Dose Finding Study of Gadopiclenol, a New Macrocyclic Contrast Agent, in MRI of Central Nervous System. Issue 3 (March 2020) - Bendszus, Martin; Roberts, Donna; Kolumban, Balint; Meza, José Alfonso; Bereczki, Daniel; San-Juan, Daniel; Liu, Benjamin P.; Anzalone, Nicoletta; Maravilla, Kenneth
Abstract : Objectives: The aim of this study was to determine a safe and effective dose of gadopiclenol, a new high relaxivity macrocyclic gadolinium-based contrast agent. Based on the contrast-to-noise ratio (CNR) as primary criterion, this new agent was compared with gadobenate dimeglumine in patients with contrast-enhancing central nervous system lesions. Methods and Materials: This phase IIb international, multicenter, double-blind, randomized, controlled, parallel dose groups, and cross-over study included adult patients with known or highly suspected lesions with disrupted blood-brain barrier. Patients were randomized to 1 of 4 doses of gadopiclenol (0.025, 0.05, 0.1, 0.2 mmol/kg) and to 1 series of 2 magnetic resonance imaging scans: gadopiclenol then gadobenate dimeglumine at 0.1 mmol/kg or vice versa. The qualitative and quantitative efficacy evaluations were performed by 3 independent off-site blinded readers. Adverse events were monitored up to 1 day after second magnetic resonance imaging. Results: The study population included 272 patients (58.5% females) with a mean (SD) age of 53.8 (13.6) years. The superiority of gadopiclenol over gadobenate dimeglumine was statistically demonstrated at 0.2 and 0.1 mmol/kg for all readers with an increase in CNR of more than 30% ( P ⩽ 0.0007). At 0.05 mmol/kg, gadopiclenol showed a CNR of similar magnitude as gadobenate dimeglumine at 0.1 mmol/kg, with no statistically significant difference. Similar results were obtained for lesion-to-brain ratio and contrast enhancement percentage, as secondary criteria. The relationship between CNR and dose of gadopiclenol was linear for all readers. Mean scores for lesion visualization variables, particularly lesion contrast enhancement, tended to be higher with gadopiclenol at 0.1 and 0.2 mmol/kg compared with gadobenate dimeglumine. All 3 readers mainly expressed an overall diagnostic preference for images with gadopiclenol at 0.1 mmol/kg (45.3%, 50.9%, or 86.8% of images) or expressed no preference (49.1%, 49.1%, or 9.4%, respectively), whereas preference for images with gadobenate dimeglumine was reported by 2 readers for 3.8% and 5.7% of the images. Predominantly, no preference was expressed when comparing images with gadopiclenol at 0.05 mmol/kg to those with gadobenate dimeglumine. Rates of adverse reactions were comparable for gadopiclenol (11.7%) and gadobenate dimeglumine (12.1%). Changes from baseline of more than 25% in serum creatinine and estimated glomerular filtration rate occurred in less than 2% of patients equally for gadopiclenol and gadobenate dimeglumine. Changes from baseline for the values of blood urea nitrogen and cystatin C were also similar between gadopiclenol and gadobenate dimeglumine. No safety concerns were detected on centralized electrocardiography readings. Conclusions: Between the doses of 0.025 and 0.2 mmol/kg of gadopiclenol, the increase in CNR is linear. Compared with gadobenate dimeglumine at 0.1 mmol/kg, the doses of 0.05 and 0.1 mmol/kg of gadopiclenol gave similar or significantly greater contrast enhancement, respectively, and thus both doses can be considered for future phase III studies. Abstract : Supplemental digital content is available in the text.